Produção de bulbos e concentração de nutrientes em folhas de alho sob a influência da calagem - Bueno de Paula , Miralda; Dias Nogueira, Francisco; Rezende Fontes, Paulo Cezar; Scheid Lopes , Alfredo (Revista Ceres, 2025)
This experiment was carried out with the aim of verifying the influence of liming on yield and nutrient concentration in garlic leaves cv. «Gigante Inconfidente’, under normal field conditions.